NILAI-NILAI YANG TERKANDUNG DALAM APRESIASI TEMBANG-TEMBANG JAWA - S. Hesti Heriwati (Gelar : Jurnal Seni Budaya, 2010)
Javanese songs (tembang) have their own charisma as educational as well as entertaining media. In the society that has not been influenced by diatonic songs and music, tembang is used as a popular media or means of rocking to sleep. However, in line with technological advance and information progress, the position of tembang is pushed aside from top position to the edge. The advancement of science and technology has an impact on all elements of life, including the existence of tembang. Starting from those facts, this writing aims at revealing the values contained in Javanese tembang as an effort for preserving Javanese culture. The appreciation of Javanese tembang is hoped to be a corridor to popularize Javanese culture we own. Understanding values will lead us to have a good knowledge of a value which can be a guideline for the society, especially the younger generation as the cultural continuer. With this kind of understanding, the younger generation are hoped to be able to show respect for the cultural heritage full of philosophical values (like religious, moral, social, heroism, tangible values). Key words : appreciation, Javanese songs, values